The Effectiveness of Integrating CALL Into Iranian EFL Contexts Challenges and Opportunities - Peyman Abbasi (Pascasarjana Universitas Negeri Makassar, 2022)
Computer and its software-programs are educational instruments that succor and facilitate instructors, teachers, and students to perform conveniently and achieve their predetermined EFL/ESL teaching and learning goals and tasks in contrast to traditional methods. This study attempts to investigate impacts of integrating CALL in Iranian EFL contexts. Researcher to collect qualitative and quantitative data, has employed mixed method strategy, and also descriptive style. As Creswell states, mixed method is the best way for research fulfillment. Total participants are 87 Iranian high school students that were dived into two separate groups. Control group (35) students that have been traditionally taught or teacher-based strategy, and experimental group (52) students that have been educated just via CALL. Subsequently, observations and findings predict and reveal that computer is useful for teacher and leaner groups to teach and learn receptive and productive L2 skills like listening, speaking, reading, and writing.